A folk remedy: royal jelly improves lung capacity in smokers: A folk remedy: royal jelly - Taşdoğan, Ali Muhittin; Tarıkçı Kılıç, Ebru; Pancar, Zarife; Özdal, Mustafa (Progress in Nutrition, 2020)
Background and Aim: Royal jelly (RJ) is one of the natural, valuable curative bee productdue to its promising health-beneficial and nutritional properties. This healthy diet possessesanti-inflammatory, antimicrobial, antioxidants, antitumor, and immunomodulatory functions which benefit in humans health and welfare,resulting in its widespread medical use. The aim of this randomized case controlled study was to determine the effect of royal jelly on the lung capacity of sedentary male smokers. Materials and Methods: The study was approved by the ethics committee of the university and consisted of 83 sedentary male and single participants aged 25-30 years without any health problems. Participation was voluntary. This case controlled design study was conducted in accordance with the ethical principles outlined by the World Medical Association’s Declaration of Helsinki. Written informed consent was obtained from participants. The sample was divided into four groups: smoker experimental (Group I: 22), non-smoker experimental (Group II: 21), smoker control (Group III: 20), and non-smoker control (Group IV: 20). The experimental groups consumed 1000 mg/day pure royal jelly between 08.00 and 10.00 am for 21 days. The control groups consumed a placebo liquid between 08.00 and 10.00 am for 21 days. Pre- and post-pulmonary function tests (PFTs) were performed. Results: Group I had significantly higher mean posttestforced expiratory volume in one second(FEV1) (1.86±0.19 L) than mean pretest FEV1 (1.76±0.05 L) while Group II had significantly higher mean posttest FEV1 (2.25±0.27 L) than mean pretest FEV1 (2.18±0.17 L) (p < 0.000). No statistically significant difference was observed in the control groups. Conclusion: PFT results before and after 1000mg/day royal jelly supplement revealed positive and significant differences.